Sy Partisi Ruang Berdasarkan Kebutuhan Pengguna Dengan Konsep Industrial - Rachmawati, Syerlina; Marwahyudi; Seftianingsih, Dina Kristiana (Fakultas Sosial Humaniora dan Seni Usahid Surakarta, 2024)
Along with the development of the era, human desires for housing are increasingly diverse, where houses are not only for carrying out daily activities and carrying on life, but also become a means of inspiration and indicate social levels in the community. The design object to be appointed is the residence of Mr. Antok Suharno which is located in the village of Mulyorejo, Mojosongo District, Boyolali Regency. The residence previously did not have a concept, the Industrial concept became the design theme plan to be implemented. The design objective is to create privacy for the living room and dining room that meets user comfort in accordance with the comfort theory by presenting a partition, functioning as a separator as well as maintaining privacy and presenting decorative value between the living room and dining room. The data collection method is by surveying, measuring and documenting the location of Mr. Antok Suharno's residence, collecting user data for each room and interviewing Mr. Antok Suharno as the owner of the house. Partitions designed to apply materials in accordance with the Industrial concept, namely with black hollow iron material, multiplex and vinyl finishing with wood motifs. The results of the partition design have a length of 180cm, a width of 30cm and a height of 200cm.